New limit on $$^{94}$$ 94 Zr double beta decay to the 1st excited state of $$^{94}$$ 94 Mo - E. Celi; M. Ješkovský; M. Laubenstein; S. S. Nagorny; V. V. Nahorna; S. Nisi; L. Pagnanini; P. Povinec; P. Wang (European Physical Journal C: Particles and Fields, 2023)
Abstract A new study of double beta decay processes in natural Zr isotopes using Zr metal samples and an ultra-low-background high-purity germanium detectors was performed at Laboratori Nazionali del Gran Sasso of INFN (Italy). Two data sets were collected with a 736.35 g and a 129.94 g Zr metal over 59.7 days and 37.3 days, respectively, and were used for a detailed analysis. A new limit on the double beta decay of $$^{94}$$ 94 Zr to the 1st excited level of $$^{94}$$ 94 Mo was set as $$T_{1/2}^{β β } > 2.1× 10^{20}~\text {year}$$ T 1 / 2 β β > 2.1 × 10 20 year , which is a factor of three better than the previous result. It is shown that the current radiopurity of Zr metal (tens of Bq/kg), produced via two methods, do not comply with the radiopurity requirements for low-background experiments. Hence, we propose to use a purified ZrCl $$_{4}$$ 4 powder in an optimized geometry as a new approach for future experiments with extended sensitivity focused on studies of rare nuclear processes in Zr isotopes.